2009
DOI: 10.1007/s10903-009-9311-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Research with Latino Farmworkers: A Systematic Evaluation of the Short CES-D

Abstract: Mental health research among Latino farmworkers is hampered by the absence of measurement evaluation that ensures farmworkers understand and can consistently and appropriately respond to questions about mental health. Cross-sectional data were obtained from 409 farmworkers via interviewer-administered survey questionnaires. Mental health was operationalized with the short-form Center for Epidemiologic Studies, Depression (CES-D) scale. The structured interviewer-administered survey questionnaires included meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 15 publications
2
37
2
Order By: Relevance
“…The study aimed to identify which interpersonal and social stressors were significantly associated with depressive symptoms and to identify significant correlates of meeting a threshold level of depressive symptoms that could be clinically significant. The average depressive symptoms score in this sample (7.22) was higher than estimates from the National Agricultural Workers Survey (Grzywacz et al (2010). In that study, the average score in the short-form CES-D was 6.92 for women and 5.87 for men.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The study aimed to identify which interpersonal and social stressors were significantly associated with depressive symptoms and to identify significant correlates of meeting a threshold level of depressive symptoms that could be clinically significant. The average depressive symptoms score in this sample (7.22) was higher than estimates from the National Agricultural Workers Survey (Grzywacz et al (2010). In that study, the average score in the short-form CES-D was 6.92 for women and 5.87 for men.…”
Section: Discussioncontrasting
confidence: 77%
“…A cut-point of 10 or higher indicated a threshold of depressive symptoms that could be clinically significant (Grzywacz et al 2006). Previous research has found that the short-form CES-D Scale had a factor structure comparable to that of the full 20-item instrument (Radloff 1977) and performed well in farmworker and non-farmworker immigrant Latino samples (Grzywacz et al 2010). Though the CES-D Scale is not a clinical tool for diagnosing depression, both the full and short-form CES-D scales have shown good to excellent concordance with clinical measures of depression in various populations (Santor et al 1995; Zich, Attkisson, and Greenfield 1990).…”
Section: Methodsmentioning
confidence: 93%
“…Patients reported their perceived general health (excellent, very good, good, fair, or poor), and depressive symptoms were measured using a validated Spanish version of the 10-item Center for Epidemiological Studies-Depression Scale (alpha = 0.79 in this dataset). 23 Medication-related problems were measured using a 7-item index with yes/no responses (see Table 2 for the specific items). Medication adherence was measured using the Morisky scale, 24 but the scale was translated de novo and was found to be not reliable (alpha < 0.61).…”
Section: Measurementsmentioning
confidence: 99%
“…Questions were selected by Spanish speaking investigators with previous experience using these scales. The supplement was translated using group translation and with native Spanish-speaking staff, and previously underwent cognitive testing and focus group analysis [12, 13]. …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the tasks involved in many facets of agricultural and the manual nature of the work raises basic questions about the applicability and relevance of scales used to evaluate workplace psychosocial stressors and their relationship to the health of farm workers. The challenge of administering standardized questionnaires and assessments to farm workers, and presumably to other Latino immigrants with a similar demographic profile, was recently illustrated [12, 13]. …”
Section: Introductionmentioning
confidence: 99%